The role of experience exchange groups in farmers' practice transitions: the case of reduced tillage in Danish conventional farming. Issue 8 (13th September 2020) - Hansen, Emilie Marie Øst; Egmose, Jonas; Lund, Søren; Hauggaard-Nielsen, Henrik
ABSTRACT: This study examined the adoption by farmers of reduced tillage practices in Danish conventional farming by means of observation and interviews with farmers involved in an experience exchange group. It identified why these farmers began reducing tillage, how they succeeded with it and what hindrances they encountered in the context of Danish conventional farming. The study found that experience exchange groups for farmers play a vital role in their rediscovery of the interrelations between agriculture and nature and of the fundamental importance of soil life and processes. The repetitive nature of interactions in a group like this may lead to the permanent adoption of sustainable practices.